Mimicking Cellular Compartmentalization in a Hierarchical Protocell through Spontaneous Spatial Organization - David Williams (ACS Central Science, 2019)
A systemic feature of eukaryotic cells is the spatial organization of functional components through compartmentalization. Developing protocells with compartmentalized synthetic organelles is, therefore, a critical milestone toward emulating one of the core characteristics of cellular life. Here we demonstrate the bottom-up, multistep, noncovalent, assembly of rudimentary subcompartmentalized protocells through the spontaneous encapsulation of semipermeable, polymersome proto-organelles inside cell-sized coacervates. The coacervate microdroplets are membranized using tailor-made terpolymers, to complete the hierarchical self-assembly of protocells, a system that mimics both the condensed cytosol and the structure of a cell membrane. In this way, the spatial organization of enzymes can be finely tuned, leading to an enhancement of functionality. Moreover, incompatible components can be sequestered in the same microenvironments without detrimental effect. The robust stability of the subcompartmentalized coacervate protocells in biocompatible milieu, such as in PBS or cell culture media, makes it a versatile platform to be extended toward studies in vitro, and perhaps, in vivo.